Charles Calvin Enslow papers - Enslow, Charles Calvin, 1836-1900.
Extracts of letters from Enslow to his wife describing his Civil War service as a soldier with the 77th Illinois Volunteers.
Negative photocopies made from originals in private hands.
Union army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Illinois Infantry Regiment, 77th (1862-1865); United States -- History -- Civil War, 1861-1865.; Soldiers